Regional Financial Development and Micro and Small Enterprises in Peru - De la Cruz, Jennifer (2025)
Empirical studies suggest that credit constraints prevent the development of Micro and Small Enterprises (MSEs). This study contributes to the analysis by exploring whether higher regional financial development affects the creation and growth of MSEs in Peru. Based on four cross-sectional databases, mainly the 2018 National Household Survey on Living Conditions and Poverty, this paper finds that there is a positive impact on entrepreneur profits; however, the effect is negative on the likelihood of running a business. Interactions between informality and financial frictions may explain this result. Informal financing emerges as an alternative in this context. This study addresses endogeneity issues by using the number of commercial bank branches per 1,000 inhabitants in 1995 as an instrument of the degree of regional financial development in 2018.